The Potential of Home-based Cardiac Rehabilitation Via Telehealth in Patients with the Post- Acute Coronary Syndrome in Indonesia: A Literature Review Study - Lutfian Lutfian; Nur Rohmawati; Nila Uli Saadah (Jurnal Ilmiah Kesehatan, 2022)
Patients with post-acute coronary syndrome (ACS) require cardiac rehabilitation.However, there were obstacles in in-hospital cardiac rehabilitation (IHCR), so that itimpacts on recurrence and a decreased quality of life. This paper analyzes the potentialof home-based cardiac rehabilitation (HBCR) via Telehealth in post-ACS patients inIndonesia. It was a literature review study. We used articles from electronic mediathrough the keywords home-based cardiac rehabilitation, Telehealth, and acute coronarysyndrome. Journals were obtained through search sites on Google Scholar, ScienceDirect, PubMed, and ProQuest. The identification criteria were using Indonesian andEnglish with the year of publication from 2015 to 2020. Then, we analysed andsynthesized eligible publications using the PRISMA method. Findings from eightjournals showed that the most common barriers for patients in in-hospital cardiacrehabilitation were logistical barriers (distance, time, functional status) and the patient'sinsufficient knowledge regarding the importance of cardiac rehabilitation. HBCR is animplementation model that has the potential as an effective solution in overcominglogistical limitations between patients and doctors. Care providers in several developedcountries have implemented HBCR. It significantly improved medication adherence,outcome, and safety profile in patients. Furthermore, virtual cardiac rehabilitationprovided the same outcome and safety profile as IHCR. Indonesia needs to developHBCR via Telehealth for secondary prevention management in patients after heartevents, especially ACS. Developing Telehealth could reduce complications andrecurrence, improve lifestyle and physical